Preparation method of porous catalyst slurry and multi-layer microporous catalyst layer and application of porous catalyst slurry and multi-layer microporous catalyst layer in membrane electrode

By using the preparation method of porous catalyst slurry in the membrane electrode catalyst layer and using mechanical stirring foaming technology to create pores inside the catalyst layer, the existing membrane electrode catalyst layer has solved the problem of low structure efficiency and susceptibility to bubble blockage, and efficient gas and liquid mass transfer and catalyst dosage savings are achieved.

CN119518002APending Publication Date: 2025-02-25SHENZHEN WENSHI HYDROGEN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576666.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing membrane electrode catalyst layer structure has problems such as poor catalytic efficiency, long mass transfer paths of gas and susceptible to pore walls and particles. Especially under high current density, bubbles are prone to block active sites and reduce the hydrogen production rate.

Method used

By using the preparation method of porous catalyst slurry, solid catalyst particles are hydrophobically modified in water containing buffer solution and hydrophobic modified substances, and foamed by mechanical stirring to form pores inside the catalyst layer to form a multi-layer microporous catalyst layer.

Benefits of technology

The efficient gas and liquid mass transfer of the catalyst layer is achieved, which reduces the amount of catalyst, especially precious metal catalysts, saves costs, and avoids the problem of bubble blocking active sites, and improves the performance of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518002A_ABST
    Figure CN119518002A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of porous catalyst slurry and a multi-layer microporous catalyst layer and application of the porous catalyst slurry and the multi-layer microporous catalyst layer in a membrane electrode. Solid catalyst particles are gradually added into water containing a buffer solution and a hydrophobic modified substance; the slurry suspension is placed in a ball mill to be subjected to homogenization treatment for preset time, and modified suspension is obtained; stirring the modified suspension in a container, and adding a high-molecular ionomer solution and a buffer solution; and carrying out primary stirring and secondary stirring through an eggbeater to obtain foamed porous catalyst slurry. Hydrophobically modified catalyst particle slurry is obtained, foaming is performed in a mechanical stirring mode, pores are formed in the slurry, the preparation mode is simple, pores in the formed slurry are uniform, the use amount of the catalyst can be greatly reduced under the condition that the catalytic efficiency is not affected, and by coating porous catalyst slurry with different pore diameters for multiple times, the catalytic efficiency of the catalyst is greatly improved. And gas molecules can be quickly generated and diffused, so that the catalytic active sites are prevented from being blocked.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for preparing a porous catalyst slurry and a multi-layer microporous catalyst layer and applications thereof in membrane electrodes. Background Art

[0002] The membrane electrode is the place where the fuel cell or electrolysis device performs electrochemical reactions. Traditionally, the membrane electrode is usually prepared by the catalyst coated gas diffusion layer electrode (CCS) method or the catalyst coated membrane (CCM) electrode method. That is, a homogeneous ink containing a catalyst, a polymer ionomer and a solvent is coated on a conductive substrate or on a conductive substrate membrane, and the catalyst particles are mutually wrapped, connected and fixed by the polymer ionomer to form a tortuous pore structure, and are fixed on the gas diffusion layer or ion exchange membrane.

[0003] Catalyst coated gas diffusion layer electrode (CCS) method Since there are problems of large ohmic resistance and easy detachment of catalyst between ion exchange membranes, the most research-focused membrane electrode preparation method is the catalyst coated membrane (CCM) electrode method.

[0004] At present, the process of preparing catalysts using CMM is affected by the state of the catalyst slurry, and only catalysts with stacked structures can be formed. This structure has poor catalytic efficiency, a long mass transfer path for liquid or gas, and is easily obstructed by pore walls and other particles. In addition, catalyst stacking is easily wrapped by ionomers used as glue to reduce exposed active sites, and the stacked structure will produce a tortuous pore structure. At high current density, it has a non-negligible effect on bubble mass transfer, and bubbles will be generated quickly and in large quantities, blocking most of the catalytic active sites, thereby reducing the hydrogen production rate. At the same time, the presence of bubbles will also cause a significant increase in ohmic resistance, which will limit the energy conversion efficiency at high current density.

[0005] In order to make the catalyst on the membrane electrode have abundant active site exposure and efficient gas or liquid mass transfer pathway, a porous catalyst layer can be used. This structure is conducive to the transmission of gas, water, electrons and ions. In the prior art, a large number of studies are devoted to improving the porosity of the catalyst layer. For example, the prior art discloses a slurry for preparing a fuel cell membrane electrode catalyst layer and its preparation, and by reasonably allocating the amount of solid catalyst, high molecular polymer, water, alcohol and non-alcohol organic solvent, a catalyst layer interface that is more conducive to gas-liquid transfer is formed.

[0006] Another prior art discloses a porous catalytic layer CCM and its preparation method and application. This technology adds water-insoluble nano-scale metal oxides (pore formers) during the pulping process, and removes the oxides by acid washing after the catalytic layer is formed to form "pores", thereby achieving pore formation in the catalytic layer and obtaining a porous catalytic layer.

[0007] Another prior art discloses a porous catalytic layer of a proton exchange membrane fuel cell membrane electrode, and a preparation method and application thereof. By adding hydrophobic gas-phase silica to the catalytic layer, it can stably exist in the catalytic layer while forming pores inside the catalyst slurry. It has good air permeability and hydrophobicity and is not easy to deform. It effectively improves the phenomenon of reduced porosity after the catalytic layer is squeezed, thereby improving the performance of the membrane electrode.

[0008] Another prior art discloses an ultrasonic spraying method for preparing a porous catalyst layer of a fuel cell membrane electrode. The method uses ultrasonic spraying to adhere a pore-forming agent solution to the surface of a proton exchange membrane. A separate flow controller is used to control the amount and mixing state of each component at different spraying times, thereby completing the gradient configuration of the porosity of the porous catalyst layer and the content of the polymer additive solution components along the thickness direction of the catalyst layer.

[0009] The first solution, namely the electrodeposition solution, can obtain a porous catalytic layer, but it consumes a lot of energy and is cumbersome to operate, and is not suitable for large-scale production and preparation. The second solution can improve the phenomenon of reduced porosity, but there will be a problem of uneven dispersion of the pore former, which requires a subsequent process of dissolving the pore former. In the actual operation of the third solution, the pore former solution cannot well control the thickness and porosity on the ion exchange membrane, and has high requirements for the sprayable slurry. Summary of the invention

[0010] Based on the technical problems existing in the background technology, the present invention proposes a method for preparing a porous catalyst slurry and a multi-level microporous catalyst layer and their application in a membrane electrode.

[0011] The present invention provides a method for preparing a porous catalyst slurry, which comprises the following components and their weight percentages:

[0012] Solid catalyst particles: 5-30wt%;

[0013] High molecular weight ionomer: 10-20wt%;

[0014] Hydroalcoholic solution: 25-50wt%;

[0015] Hydrophobic modified substance: 1-5wt%;

[0016] Buffer solution 1-5wt%.

[0017] Furthermore, the solid catalyst particles include cathode catalysts and anode catalysts, wherein the cathode catalysts include but are not limited to platinum-loaded carbon particles and palladium-loaded carbon particles, and the anode catalysts include but are not limited to iridium-containing precious metal oxide catalysts, ruthenium-containing precious metal oxide catalysts and iron-cobalt-nickel transition metal layered double hydroxide catalysts.

[0018] Furthermore, the hydroalcohol solution includes ultrapure water and one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol, and the volume mixing ratio is 5:1.

[0019] Furthermore, the hydrophobic modified substance includes but is not limited to butyric acid, n-hexylamine, propyl gallate and butyl gallic acid.

[0020] Furthermore, the buffer solution includes hydrochloric acid solution and sodium hydroxide solution.

[0021] Further, the following steps are included:

[0022] S1, gradually adding the solid catalyst particles into water containing the buffer solution and the hydrophobic modified substance to obtain a slurry suspension;

[0023] S2, placing the slurry suspension in a preset ball mill for homogenization treatment for a preset time to obtain a modified suspension;

[0024] S3, dissolving the polymer ionomer in the water-alcohol solution to obtain a polymer ionomer solution;

[0025] S4, placing the modified suspension in a preset container and stirring, while adding the polymer ionomer solution;

[0026] S5, adding the buffer solution until a preset pH value is reached;

[0027] S6, adjusting the amount of the polymer ionomer solution until the solid particle content is 15-25 wt % to obtain a catalyst particle slurry;

[0028] S7, placing the catalyst particle slurry in a preset egg beater for primary stirring and secondary stirring to perform foaming to obtain a porous catalyst slurry.

[0029] Furthermore, the solid content of the slurry suspension is 50 vol%, and the pH value is 4.9.

[0030] Furthermore, the preset time is greater than or equal to 18 hours, and the preset pH value is 4.75.

[0031] Furthermore, the rotation speed of the first stirring is 900 rpm, and the stirring time is 5 min; the rotation speed of the second stirring is 1500 rpm, and the stirring time is 10 min.

[0032] A multi-layer microporous catalyst layer includes S1-S7 and is prepared by multiple slit coating on a preset ion exchange membrane.

[0033] The present invention has the following beneficial effects: the present application adds solid catalyst particles to water containing a buffer solution and a hydrophobic modification substance to obtain a hydrophobically modified catalyst particle slurry, and foams by mechanical stirring to form pores inside the slurry. This preparation method is simple in process and can be mass-produced on a large scale. The formed slurry has good rheological properties and can be well applied to the method of preparing membrane electrodes by extrusion coating. The pores inside the formed slurry are uniform and small in size, and can be applied to coating ultra-thin catalyst coatings. By forming pores inside the catalyst layer, the amount of catalyst can be greatly reduced without affecting the catalytic efficiency, especially for catalyst materials that require precious metals as catalysts, which can save costs. By repeatedly applying porous catalyst slurries with different pore sizes, and the microporous structure has the smallest pore size at the bottom layer and the largest pore size at the top layer, it is beneficial to quickly generate gas molecules in the water electrolysis device and quickly diffuse them to avoid clogging the catalytic active sites. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 A process flow chart of a method for preparing a porous catalyst slurry proposed by the present invention;

[0035] Figure 2 This is a diagram showing the internal pore structure of the porous catalyst slurry prepared in Example 1 of the present invention;

[0036] Figure 3 is a bubble pore size distribution diagram of the porous catalyst slurry formed by different rotation speeds in Example 2 of the present invention;

[0037] Figure 4 This is a schematic diagram of a multi-layer microporous catalyst layer formed by multiple coatings in Example 2 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0040] A method for preparing a porous catalyst slurry, comprising the following components and their weight percentages:

[0041] Solid catalyst particles: 5-30wt%;

[0042] High molecular weight ionomer: 10-20wt%;

[0043] Hydroalcoholic solution: 25-50wt%;

[0044] Hydrophobic modified substance: 1-5wt%;

[0045] Buffer solution 1-5wt%.

[0046] In this embodiment, 5-30wt% of solid catalyst particles, 10-20wt% of polymer ionomer, 25-50wt% of water-alcohol solution, 1-5wt% of hydrophobic modified substance and 1-5wt% of buffer solution are used as raw materials for preparation. Specifically, the solid catalyst particles include cathode catalyst and anode catalyst, wherein the cathode catalyst can be ultrafine carbon particles loaded with platinum or ultrafine carbon particles loaded with palladium; the anode catalyst can be a layered double hydroxide catalyst containing iridium (Ir) precious metal oxide catalyst, a ruthenium (Ru) precious metal oxide catalyst or an iron-cobalt-nickel transition metal. The polymer ionomer is one or more of the Nafion, Vensogen or PiperION series products. The water-alcohol solution is a mixed solution of ultrapure water and one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol, and the volume mixing ratio is 5:1, wherein the volume mixing ratio is the ratio of each volume ratio in the mixture. The hydrophobic modified substance is butyric acid, n-hexylamine, propyl gallate and butyl gallic acid or other short-chain amphiphilic molecules. The buffer solution is hydrochloric acid solution and sodium hydroxide solution.

[0047] Refer to the attached Figure 1 , a method for preparing a porous catalyst slurry, comprising the following steps:

[0048] S1, gradually adding solid catalyst particles into water containing a buffer solution and a hydrophobic modification substance to obtain a slurry suspension;

[0049] S2, placing the slurry suspension in a preset ball mill for homogenization treatment for a preset time to obtain a modified suspension;

[0050] S3, dissolving the polymer ionomer in a water-alcohol solution to obtain a polymer ionomer solution;

[0051] S4, placing the modified suspension in a preset container and stirring it, while adding the polymer ionomer solution;

[0052] S5, adding a buffer solution until a preset pH value is reached;

[0053] S6, adjusting the amount of the polymer ionomer solution until the solid particle content is between 15 and 25 wt % to obtain a catalyst particle slurry;

[0054] S7, placing the catalyst particle slurry in a preset egg beater for primary stirring and secondary stirring to perform foaming, thereby obtaining a porous catalyst slurry.

[0055] In the above steps, firstly, a catalyst particle slurry suspension and surface hydrophobic modification are prepared: 5-30wt% of solid catalyst particles are gradually added to water containing 1-5wt% of buffer solution and 1-5wt% of hydrophobic modification material to obtain a slurry suspension with a solid content of 50vol% and a pH value of 4.9. Then, the slurry suspension is placed in a ball mill, which homogenizes the slurry suspension and runs for at least 18 hours to obtain a modified suspension. The polymer ionomer is placed in a water-alcohol solution for dissolution to obtain a polymer ionomer solution. Then mechanical stirring and foaming are carried out: the modified suspension is placed in a container for stirring, 10-20wt% polymer ionomer solution is added during stirring, and then a buffer solution is added until the pH value is adjusted to 4.75; at the same time, the solid particle content in the modified suspension is adjusted by adjusting the amount of the added polymer ionomer solution until the solid particle content is 15-25wt%, and a catalyst particle slurry is obtained; finally, a hand-held egg beater is stirred at a speed of 900rpm for 5min, and then the speed is increased to 1500rpm and stirred for 10min to foam until the volume no longer changes, and a porous catalyst slurry is obtained. The present application adds solid catalyst particles to water containing a buffer solution and a hydrophobic modified substance to obtain a hydrophobically modified catalyst particle slurry, and foams by mechanical stirring to form pores inside the slurry. This preparation method is simple in process, can be mass-produced on a large scale, and the resulting slurry has good rheological properties, which can be well applied to the method of preparing membrane electrodes by extrusion coating. The pores inside the formed slurry are uniform and small in size, and can be applied to coating ultra-thin catalyst coatings. By creating holes inside the catalyst layer, the amount of catalyst used can be greatly reduced without affecting the catalytic efficiency, especially for catalyst materials that require precious metals as catalysts, which can save costs.

[0056] A multi-layer microporous catalyst layer includes S1-S7 and is prepared by multiple slit coating on a preset ion exchange membrane.

[0057] Specifically, the present application utilizes a surface hydrophobic catalyst, i.e., a hydrophobic modified substance, to continuously form foam during mechanical stirring, and introduces bubbles into the original catalyst particle slurry, and solidifies the bubbles in the catalyst particle slurry to obtain a porous catalyst slurry. After solidification, a uniformly distributed porous structure will be formed. By repeatedly slit-coating a porous catalyst slurry of different pore sizes on the ion exchange membrane, and the microporous structure has the smallest pore size at the bottom layer and the largest pore size at the top layer, this structure is conducive to the rapid generation of gas molecules in the water electrolysis device, and rapid diffusion, to avoid blockage of the catalytic active sites.

[0058] In summary: in the specific implementation, first, 5-30wt% of solid catalyst particles are gradually added to water containing 1-5wt% of buffer solution and 1-5wt% of hydrophobic modified substance to obtain a slurry suspension with a solid content of 50vol% and a pH value of 4.9; then the slurry suspension is placed in a ball mill, and the ball mill is used to homogenize the slurry suspension and run for at least 18 hours to obtain a modified suspension; then a polymer ionomer solution is prepared, that is, the polymer ionomer is placed in a water-alcohol solution for dissolution. The modified suspension is then placed in a container for stirring, and 10-20wt% polymer ionomer solution is added during stirring, and a buffer solution is added until the pH value is adjusted to 4.75; At the same time, the amount of the added polymer ionomer solution is adjusted until the solid particle content is 15-25wt%, and a catalyst particle slurry is obtained; Finally, a handheld egg beater is stirred at a speed of 900rpm for 5min, and then the speed is increased to 1500rpm and stirred for 10min until the volume no longer changes, and a porous catalyst slurry is finally obtained; Finally, multiple slit coatings are performed on the ion exchange membrane to obtain a multi-level microporous catalyst layer. The preparation process of the present application is simple, and large-scale batch production can be carried out. Hydrophobic modified catalyst particles are used, and the modified suspension is mechanically foamed to form pores inside the catalyst slurry. The formed slurry has good rheological properties and can be well applied to the method of preparing membrane electrodes by extrusion coating, and the pores inside the formed slurry are uniform and small in size, which can be applied to coating ultra-thin catalyst coatings. By forming pores inside the catalyst layer, the amount of catalyst can be greatly reduced without affecting the catalytic efficiency. By controlling the bubble size in the coating slurry and coating it multiple times, a multi-level microporous structure can be constructed on the MEA (ethanolamine) catalyst layer.

[0059] Refer to the attached Figure 1 , is a method for preparing a porous catalyst slurry in one embodiment of the present invention, wherein:

[0060] Example 1

[0061] A porous catalyst slurry is prepared according to the following steps:

[0062] S1. 20 g of solid catalyst particles were gradually added to 60 mL of water, and the pH value was adjusted to 4.9 using a buffer solution to obtain a slurry suspension;

[0063] S2. The slurry suspension is placed in a polyethylene grinding jar and gently stirred. At the same time, an aqueous solution containing butyric acid and NaOH (or HCl) is slowly added dropwise to avoid local particle agglomeration. The diameter of the alumina balls in the polyethylene grinding jar is 10 mm, and the ratio of balls to powder is 2:1. The amount of butyric acid added is 50 mol / L.

[0064] S3. Place in a ball mill and homogenize for at least 18h to obtain a modified suspension;

[0065] S4. Dissolving 10 g of the polymer ionomer in 50 mL of a water-alcohol solution to obtain a 20 wt % polymer ionomer solution;

[0066] S5. The modified suspension is placed in a container and stirred, and 10 mL of a polymer ionomer solution is added, and a buffer solution is added to adjust the pH to 4.75 and the amount of the polymer ionomer solution is adjusted until the solid particle content reaches 25 wt %;

[0067] S6. The mixture was stirred at 900 rpm for 5 min with a hand-held egg beater, and then the speed was increased to 1500 rpm for 10 min until the volume of the modified suspension did not change, thereby obtaining a porous catalyst slurry;

[0068] S7. Place the porous catalyst slurry in a coating machine container and assemble the membrane electrode on the ion exchange membrane using an extrusion slit coating method.

[0069] Example 2

[0070] A porous catalyst slurry and a multi-layer microporous catalyst layer are prepared according to the following steps:

[0071] S1. 20 g of solid catalyst particles were gradually added to 60 mL of water, and the pH value was adjusted to 4.9 using a buffer solution to obtain a slurry suspension;

[0072] S2. The slurry suspension is placed in a polyethylene grinding jar and stirred slightly. At the same time, an aqueous solution containing butyric acid and NaOH (or HCl) is slowly added dropwise to avoid local particle agglomeration. The diameter of the alumina balls in the polyethylene grinding jar is 10 mm, and the ratio of balls to powder is 2:1. The amount of butyric acid added is 50 mol / L.

[0073] S3. Place in a ball mill and homogenize for at least 18h to obtain a modified suspension;

[0074] S4. Dissolving 10 g of the polymer ionomer in 50 mL of a water-alcohol solution to obtain a 20 wt % polymer ionomer solution;

[0075] S5. The modified suspension was placed in a container and stirred, and 10 mL of the polymer ionomer solution was added, and a buffer solution was added to adjust the pH to 4.75 and the amount of water was adjusted until the solid particle content reached 25 wt % to obtain a catalyst particle slurry;

[0076] S6. Prepare three portions of the above catalyst particle slurry, first stir them with a hand-held egg beater at a stirring speed of 900 rpm for 5 minutes, and then stir them at speeds of 1000 rpm, 5000 rpm and 10000 rpm for 10 minutes respectively to obtain a first foaming slurry, a second foaming slurry and a third foaming slurry.

[0077] S7. sequentially apply the third foaming slurry, the second foaming slurry and the first foaming slurry on the ion exchange membrane to prepare a membrane electrode.

[0078] That is, the slurry treatment process in Example 2 is the same as that in Example 1, but after stirring with a hand-held egg beater at a stirring speed of 900 rpm for 5 minutes, stirring is performed at speeds of 1000 rpm, 5000 rpm and 10000 rpm for 10 minutes respectively.

[0079] Comparative Example 1

[0080] S1. 20 g of solid catalyst particles were gradually added to 60 mL of water, and the pH value was adjusted to 4.9 using a buffer solution to obtain a slurry suspension;

[0081] S2. The slurry suspension is placed in a polyethylene grinding jar and gently stirred. At the same time, an aqueous solution containing butyric acid and NaOH (or HCl) is slowly added dropwise to avoid local particle agglomeration. The diameter of the alumina balls in the polyethylene grinding jar is 10 mm, and the ratio of balls to powder is 2:1. The amount of butyric acid added is 50 mol / L.

[0082] S3. Place in a ball mill and homogenize for at least 18h to obtain a modified suspension;

[0083] S4. Dissolving 10 g of the polymer ionomer in 50 mL of a water-alcohol solution to obtain a 20 wt % polymer ionomer solution;

[0084] S5. The modified suspension is placed in a container and stirred, and 10 mL of a polymer ionomer solution is added, and a buffer solution is added to adjust the pH to 4.75 and the amount of the polymer ionomer solution is adjusted until the solid particle content reaches 25 wt %;

[0085] S6. Coat on an ion exchange membrane to prepare a membrane electrode.

[0086] That is, the slurry ratio and preparation process in Comparative Example 1 are the same as those in Example 1, except that there is no subsequent mechanical stirring and foaming process, and the multilayer coating method is the same as in Example 2.

[0087] Figure 2 This is a diagram of the internal pore structure of the porous catalyst slurry in Example 1; Figure 3 The pore size distribution diagram of the slurry bubbles formed by different rotation speeds in Example 2; Figure 4 Schematic diagram of a multi-layer microporous catalyst layer formed by multiple coatings in Example 2.

[0088] Depend on Figure 2 It can be seen that the pores of the porous catalyst slurry prepared in Example 1 are uniform and small in size. Figure 3 It can be seen that at different stirring speeds, the pore sizes of the porous catalyst slurry are different; the faster the stirring speed, the smaller the pore size. Figure 4 It can be seen that the multi-layer microporous catalyst layer formed after multi-layer coating has the smallest pore size at the bottom and gradually increases upwards, and the pore size of the top layer is the largest.

[0089] Compared with the prior art, the present application adds solid catalyst particles to water containing a buffer solution and a hydrophobic modified substance to obtain a hydrophobically modified catalyst particle slurry, and foams by mechanical stirring to form pores inside the slurry. The preparation method is simple, and the pores inside the formed slurry are uniform and small in size. By forming pores inside the catalyst layer, the amount of catalyst can be greatly reduced without affecting the catalytic efficiency. After the porous catalyst slurry is coated multiple times, a microporous structure with the smallest bottom layer and the largest top layer is formed, which is conducive to the rapid generation of gas molecules in a water electrolysis device or a fuel cell, and rapid diffusion, which can avoid clogging of the catalytic active sites.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a porous catalyst slurry, characterized in that: The following ingredients and weight percentages composition: Solid catalyst particles: 5-30wt%; High molecular weight ionomer: 10-20wt%; Hydroalcoholic solution: 25-50wt%; Hydrophobic modified substance: 1-5wt%; Buffer solution 1-5wt%.

2. The method for preparing a porous catalyst slurry according to claim 1, characterized in that: The solid catalyst particles include cathode catalysts and anode catalysts, wherein the cathode catalysts include but are not limited to platinum-loaded carbon particles and palladium-loaded carbon particles, and the anode catalysts include but are not limited to iridium-containing precious metal oxide catalysts, ruthenium-containing precious metal oxide catalysts and iron-cobalt-nickel transition metal layered double hydroxide catalysts.

3. The method for preparing a porous catalyst slurry according to claim 1, characterized in that: The hydroalcohol solution includes ultrapure water and one or more of methanol, ethanol, ethylene glycol, propanol and isopropanol, and the volume mixing ratio is 5:

1.

4. The method for preparing a porous catalyst slurry according to claim 1, characterized in that: The hydrophobic modifying substances include, but are not limited to, butyric acid, n-hexylamine, propyl gallate and butyl gallic acid.

5. The method for preparing a porous catalyst slurry according to claim 1, characterized in that: The buffer solution includes hydrochloric acid solution and sodium hydroxide solution.

6. The method for preparing a porous catalyst slurry according to claim 1, characterized in that: The following steps are involved: S1, gradually adding the solid catalyst particles into water containing the buffer solution and the hydrophobic modified substance to obtain a slurry suspension; S2, placing the slurry suspension in a preset ball mill for homogenization treatment for a preset time to obtain a modified suspension; S3, dissolving the polymer ionomer in the water-alcohol solution to obtain a polymer ionomer solution; S4, placing the modified suspension in a preset container and stirring, while adding the polymer ionomer solution; S5, adding the buffer solution until a preset pH value is reached; S6, adjusting the amount of the polymer ionomer solution until the solid particle content is 15-25 wt % to obtain a catalyst particle slurry; S7, placing the catalyst particle slurry in a preset egg beater for primary stirring and secondary stirring to perform foaming to obtain a porous catalyst slurry.

7. The method for preparing a porous catalyst slurry according to claim 6, characterized in that: The solid content of the slurry suspension is 50 vol%, and the pH value is 4.

9.

8. The method for preparing a porous catalyst slurry according to claim 6, characterized in that: The preset time is greater than or equal to 18 hours, and the preset pH value is 4.

75.

9. The method for preparing a porous catalyst slurry according to claim 6, characterized in that: The rotation speed of the first stirring was 900 rpm, and the stirring time was 5 min; the rotation speed of the second stirring was 1500 rpm, and the stirring time was 10 min.

10. A porous catalyst slurry, characterized in that: The porous catalyst slurry is prepared by the preparation method of any one of claims 1 to 9.

11. A multi-layer microporous catalyst layer, characterized in that: The method is obtained by performing multiple slit coating on a preset ion exchange membrane according to claim 10.

12. The multi-layered microporous catalyst layer according to claim 11, characterized in that: Used in fuel cell membrane electrodes or water electrolysis hydrogen production devices.